from the origin,chords are drawn to the circle square(x-1) +square(y)=1.the equation of the locus of the mid pt. of these chord is....

2 years ago

Share

Answers : (2)

                                        x^2+y^2=x
                                        
2 years ago
                                        

O(0,0) lies on the circle.


general form of any point on this circle is given by (-g+r(cosØ),-f+r(sinØ)) hence here it is P(1+1(cosØ),1(sinØ)).


thus for mid pt. of chord OP:


x= (0+1+1cosØ)/2 =>(1+cosØ)/2    (1)


y=sinØ/2;     (2)


from (1) and (2), (cosØ)^2= (2x-1)^2,   (3)


                          (sinØ)^2=(2y)^2;     (4)


adding (3) and (4)


     sqr(2x-1)+sqr(2y)=1,


 or x^2 +y^2-x=0 ,which is the required eq.


 

2 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
In a triangle a^2+b^2+c^2-ac-root3 *ab=0 then the triangle is necessarily
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 3 months ago
How does find the slope of a circle. Please give me an easy method which works all the time. Thanks
 
 
Dear student, We know that atany pointP having the coordinates (x,y)on the unit circle satisfies the relation Hence, we get that Now we can use the usual parameterization of the circle, i.e....
  img
Sumit Majumdar 2 months ago
The age of a man is four times that of his son. Five years ago, the man was nine times as old as his son at that time. The present age of the man is
 
 
Let the age of son be x. Hence, theage of father = 4x Age of son 5 years ago = x - 5 Age of father 5 years ago = 4x - 5 Its given that, 5 years ago the man was 9 times old as his son. ? 4x -...
  img
bharat bajaj 4 months ago
 
Let the age of son be x. Hence, theage of father = 4x Age of son 5 years ago = x - 5 Age of father 5 years ago = 4x - 5 Its given that, 5 years ago the man was 9 times old as his son. ? 4x -...
  img
bharat bajaj 4 months ago
See attachment sir please explain this question …...I’ll be very great full
 
 
Ans: Thanks & Regards Jitender Singh IIT Delhi askIITians Faculty
  img
Jitender Singh 2 months ago
 
 
milind 2 months ago
 
 
milind 2 months ago
evaluate ∫ (sqrt(x)( ax^2 + bx + c)) dx
 
 
∫ (sqrt(x)( ax^2 + bx + c)dx =​∫ (x^1/2(ax^2 +bx +c)dx =​∫ (ax^5/2 +bx^3/2 +cx^1/2)dx =2​ax^7/2 /7 +2bx^5/2 /5 +2cx^3/2 /3 +K {we know that​∫x^ndx =(x^(n+1) /(n+1)} Here K is...
  img
Sunil Raikwar one month ago
 
make ax 2 +bx+c in to form of a((x-b/2) 2 +(c -b 2 /4)). then put (x-b/2)=(c-b 2 /4)^.5*tany. then integrate it. simple
 
Karthick vel one month ago
integrate 1/(a+bcosx)^2 dx
 
 
Ans:Hello student, please find answer to your question Now, simply use the standard form & partial farction
  img
Jitender Singh 2 months ago
View all Questions »